Development and testing of a fluorescent fiber solar concentrator for remote daylighting - Wang, C.; Abdul-Rahman, H.; Rao, S.P. (American Society of Civil Engineers (ASCE), 2010)
Conventional solar concentrators and normal luminescent solar concentrators have their difficulties in reticulation and a tracking mechanism is always needed. This article introduces a new design of an optical fiber solar concentrator, which is a 1,200 mm x 1,200 mm polymethyl methacrylate plate consisting of 150 pieces of three-color 1-m long Phi 2-mm fluorescent fibers. The concentrator is fabricated and is mounted on a university building roof and the concentrated light is transported to a remote dark room through 10-m long Phi 2-mm clear optical fibers. A 6-month outdoor testing for its remote indoor daylighting application has been conducted. The reasonable radiation-to-radiation efficiency with a mean value of 0.057, the acceptable lighting effect up to 114.1 1m, and the light-to-light efficiency of 0.58% reveal this fiber solar concentrator a potential in remote indoor daylighting for the application in building integration. The light produced by this device presents a good match to the direct sunlight in color.